Unconscious bias toward employee performance in Perak Hotel Industry - Chu, Chin Fai; Non, Kee Wei; Tan, Chong Hau; Teo, Lai Teng (2020)
This research study will investigate the “Unconscious bias towards employee performance in Perak hotel industry”. In this study, researchers have investigated the relationship between affinity bias, confirmation bias, halo effect and bandwagon effect with employee performance. The reason that we focus on Perak hotel industry is because Perak hotel industry plays an important role in promoting the economy growth of Malaysia, but it is under strong pressure in the unstable marketplace today, and actually the unconscious bias is affected in the employee performance for hotel industry. The data of this study will be collected from employees who working in hotel. There is total 30 set questionnaires were distributed by using convenient sampling method. Statistical Package for the Social Sciences (SPSS) version 16 had been used in order to run the reliability analysis, frequency analysis, explain the correlation coefficient analysis, and test of hypothesized relationships between the independent variables dependent variable. The results of the analysis confirmed that there is a positive relationship between Affinity Bias, Confirmation Bias, Halo Effect, Bandwagon effect and Employee performance.